Implementation of the utilization of PT BNI (Persero) Tbk CSR funds at Raden Intan State Islamic University Lampung - Davin (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2021)
CSR is a company's concern for the interests of other parties more broadly, not just the interests of the company itself. For companies that consistently implement CSR in their activities, in the long term they will benefit in the form of trust from their stakeholders. The purpose of this study was to determine the implementation of the utilization of CSR funds of PT BNI (Persero) at Raden Intan State Islamic University, Lampung. The research method used in this study uses qualitative methods. The results of this study indicate that the implementation of the utilization of CSR funds of PT BNI (Persero) at UIN Raden Intan Lampung is quite good, namely the provision of pensions and allowances; education funds; contribute to improving the quality of life of the community and the environment.